A novel combined power and cooling cycle design and a modified conditional exergy destruction approach. (1st April 2021) - Singh, Adityabir; Das, Ranjan
Highlights: A new combined power and cooling cycle design with common absorber is proposed. New scheme to address conditional nature of exergy destruction is introduced. Dual-mode dragonfly optimization is introduced for minimizing exergy destruction. Power, cooling capacity and exergy efficiency improve by 1.84, 6.74, and 1.33 times. Exergy destruction increases by 1.35 times due to its conditional nature. Abstract: This paper introduces a new combined power and cooling cycle ( CPCC ) formed by the integration of a modified Kalina and Goswami cycles sharing a common absorber that in turn demands for internal rectification in the former cycle. Unlike most of the conventional studies which are aimed at minimizing the overall exergy destruction of the cycle ( Ė Dx, OC ), this work clarifies that such a practice does not ensure the optimized attainment of total turbine work output (Ẇ TR ), cooling output (Ċ cooling ) and exergy efficiency (η exergy ) of the cycle. Therefore, this conditional nature of Ė Dx, OC is addressed here through the optimization of an integrated objective function addressing each of the desired performance parameters using a dual-mode dragonfly algorithm. The optimization is performed for a range of strong solution concentration, boiler temperature and pressure, in which only the first two parameters are independently varying, while the third is dependent on the previous parameters to ensure partial vaporization. The temperature of the strong solution is kept below its bubble temperature while recovering heat from the hot liquid condensate so that there is no vaporization before entering the boiler. When the present optimization approach is performed for a given set of operational parameters, the values of Ẇ TR, Ċ cooling and η exergy are observed to improve by 1.84, 6.74, and 1.33 times, respectively with 1.35 times compromise in Ė Dx, OC, with respect to the conventional practice. The temperature of the strong solution is kept below its T bubble while recovering heat from the liquid condensate by performing pinch point calculations.